2020
DOI: 10.1158/1541-7786.mcr-19-0585
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the ATR–CHK1 Pathway in Ewing Sarcoma Cells Causes DNA Damage and Apoptosis via the CDK2-Mediated Degradation of RRM2

Abstract: Inhibition of ribonucleotide reductase (RNR), the rate-limiting enzyme in the synthesis of deoxyribonucleotides, causes DNA replication stress and activates the ATR-CHK1 pathway. Notably, a number of different cancers, including Ewing sarcoma tumors, are sensitive to the combination of RNR and ATR-CHK1 inhibitors. However, multiple, overlapping mechanisms are reported to underlie the toxicity of ATR-CHK1 inhibitors, both as single-agents and in combination with RNR inhibitors, toward cancer cells. Here, we ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 65 publications
6
58
0
Order By: Relevance
“…Deregulated expression, prognostic value as well as therapeutic exploitation of RRM2 has been reported in various types of cancer over the past decade including prostate cancer [11,12], glioblastoma [13], colorectal cancer [14], melanoma [15], Ewing sarcoma [10], cervical [16] and breast cancer [17,18]. Besides the finding of RRM2 as part of a four-gene prognostic signature in high-risk neuroblastoma and a recent report with limited data showing that siRNA mediated knockdown in SH-SY5Y cells caused a cell cycle arrest concomitant with apoptosis induction [19], the functional role of RRM2 in neuroblastoma tumorigenesis has remained unexplored thus far.…”
Section: Functional In Vitro and In Vivo Validation Of Rrm2 As A Novementioning
confidence: 99%
“…Deregulated expression, prognostic value as well as therapeutic exploitation of RRM2 has been reported in various types of cancer over the past decade including prostate cancer [11,12], glioblastoma [13], colorectal cancer [14], melanoma [15], Ewing sarcoma [10], cervical [16] and breast cancer [17,18]. Besides the finding of RRM2 as part of a four-gene prognostic signature in high-risk neuroblastoma and a recent report with limited data showing that siRNA mediated knockdown in SH-SY5Y cells caused a cell cycle arrest concomitant with apoptosis induction [19], the functional role of RRM2 in neuroblastoma tumorigenesis has remained unexplored thus far.…”
Section: Functional In Vitro and In Vivo Validation Of Rrm2 As A Novementioning
confidence: 99%
“…ATR is activated by SSBs and replicative stress (RS) to maintain genomic stability [15,37,36]. ES cells, which are de cient in BRCA1mediated HR, suffer from permanent RS, rely on ATR-CHK1 pathways and are thus sensitive to ATRi [10,6,2,3]. In addition, we found that both ATRi and HSP90i share a set of common molecular targets, involved in cell vitality and proliferation, and ER stress response.…”
Section: Discussionmentioning
confidence: 91%
“…BALB-CTA tests and experiments in colon cancer cells showed the therapeutic potential of AUY-VE beyond ES cells. Since HSP90i and ATRi are already used to treat various types of cancer in clinical phase I/II trials [14,61,15,10,16,57], their combinations could further increase their effectiveness and improve the prognosis of patients, especially for BRCA-and p53de cient tumor entities. Figure S3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One group showed that the WEE1 inhibitor, MK-1775, exacerbated the cytotoxic effects of a DNA replication stress drug, gemcitabine, in MPNST, UPS, and OS cell lines [211]. More recently, studies in EwS cells showed that inhibition of the ATR-CHK1 checkpoint pathway activates CDK2, which enhances DNA replication stress by targeting a subunit of the ribonucleotide reductase enzyme for proteasomal degradation [212]. Those findings led to concurrent targeting of ATR-CHK1 and WEE1 pathways, which killed EwS cells in a highly synergistic fashion.…”
Section: Cdk-targeted Anti-cancer Therapymentioning
confidence: 99%